2015
DOI: 10.1186/s40064-015-1493-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory properties of mutolide isolated from the fungus Lepidosphaeria species (PM0651419)

Abstract: Mutolide an anti-inflammatory compound was isolated from the coprophilous fungus Lepidosphaeria sp. (PM0651419). The compound mitigated LPS-induced secretion of pro-inflammatory cytokines TNF-α and IL-6 from THP-1 cells as well as human peripheral blood mononuclear cells (hPBMCs). Mutolide also inhibited secretion of another pro-inflammatory cytokine IL-17 from anti-hCD3/anti-hCD28 stimulated hPBMCs. NF-κB is the major transcription factor involved in the secretion of pro-inflammatory cytokines including IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
4
10
0
Order By: Relevance
“…12 Iss. carry out the biotransformation at 0.5 mM of AgNO 3 , thus strengthening our belief on their biotransformation potential [35] The crystalline nature of biosynthesised AgNPs in this study using coprophilous PM0651419 fungus is comparable to reported literature on extracellular biosynthesis of AgNPs like the ones obtained from Fusarium oxysporum [54] and Penicillium brevicompactum [46]. Silver has been used since historical times as silver nitrate and silver sulfadiazine in the treatment of burns and infections [55].…”
supporting
confidence: 85%
“…12 Iss. carry out the biotransformation at 0.5 mM of AgNO 3 , thus strengthening our belief on their biotransformation potential [35] The crystalline nature of biosynthesised AgNPs in this study using coprophilous PM0651419 fungus is comparable to reported literature on extracellular biosynthesis of AgNPs like the ones obtained from Fusarium oxysporum [54] and Penicillium brevicompactum [46]. Silver has been used since historical times as silver nitrate and silver sulfadiazine in the treatment of burns and infections [55].…”
supporting
confidence: 85%
“…The increasing resistance of pathogenic microorganisms to antibiotics in the world, and recently in Algeria, leading to the resurgence of more complex infections (Baba Ahmed-Kazi Tani and Arlet, 2014), has pushed researchers to discover new bioactive molecules. The capacity of endophytic fungi to biosynthesize bioactive secondary metabolites (more than 20.000 bioactive molecules) (Marson Ascêncio et al, 2014) and their various biological activities such as antimicrobial, anti-viral, anticancer, antioxidant, antidiabetic, and antiinflammatory activity (Sadrati et al, 2013;Bashyal et al, 2014;Shah et al, 2015;Jouda et al, 2016a;Pan et al, 2016;Singh and Kaur 2016;Yao et al, 2017) have made this fungus to be important, as an important source of new bioactive secondary metabolites potentially useful for human medicine and other domains.…”
Section: Introductionmentioning
confidence: 99%
“… 27 29 Inflammation induced by carrageenan produces the cardinal features of inflammation and has been shown to mimic human clinical conditions. 30 , 31 Natural products possess clinical effectiveness in the prevention and treatment of inflammatory conditions 32 and their therapeutic prospective has been advocated to the marked anti-inflammatory properties in both in vivo animal models 33 , 34 and in vitro human cells’ 35 37 inflammation paradigms. Chromones exhibit putative anti-inflammatory properties.…”
Section: Resultsmentioning
confidence: 99%